Factors associated with toothache in 12-year-old adolescents in a southeastern state of Brazil - Nildelaine Cristina Costa; Mauro Henrique Nogueira Guimarães Abreu; Rafaela Silveira Pinto; Fabiana Vargas-Ferreira; Renata Castro Martins (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: This cross-sectional study evaluated factors associated with toothache in 12-year-old adolescents from the state of Minas Gerais in Brazil. Secondary data were collected from the SB Minas Gerais 2012 epidemiological survey. The dependent variable was toothache in the past 6 months. The independent variables were grouped into two levels: individual (sex, ethnic group, family income, periodontal condition, dental caries, dental treatment needs, and type of service used) and contextual (allocation factor, Human Development Index, Gini coefficient, gross domestic product, unemployment, illiteracy, basic sanitation, garbage collection, family income, half or a quarter of a minimum wage, primary healthcare coverage, primary oral healthcare team coverage, oral health technician, access to individual dental care, and supervised tooth brushing). A multilevel analysis was performed using the Hierarchical Linear and Nonlinear Modeling Software Program to assess the association of individual and contextual variables with toothache in the last 6 months. The prevalence of toothache in the last six months among the adolescents of this study was 19.1%. An association was found with family income (p <0.001), dental caries (p <0.001), primary oral healthcare team coverage (p = 0.015) and oral health technician (p = 0.008). Socioeconomic conditions and the most prevalent oral diseases, such as dental caries, as well as the use of public services, were related to toothache in adolescents aged 12 years. These findings reinforce the need to develop and implement public policies to address the oral health problems of this population.